The Relationship of Mother's Knowledge Regarding Food Presentation With Appetite Stunting Children In The Working Area of The Loka Puskesmas Bantaeng - Hamdana; Nursyafika; Haerani (Comprehensive Health Care, 2024)
Background: According to the World Health Organization (WHO), stunting is defined as a growth factor that describes the failure to achieve growth potential as a result of suboptimal health and/or nutritional status, chronic nutritional problems caused by a lack of food for a long time, usually because the diet does not meet needs. nutrition. The problem of stunting starts in the womb and is not realized until the child is two years old. The prevalence of stunting in Bantaeng district is 5.84% and there is a high prevalence of stunting in local health centers at 211 (25.53%) and the highest prevalence of stunting in villages is in Bonto Tallas, namely 55 and the lowest is at Bisappu Community Health Center at 0 .58% (Dinkes 2023). Objective: to find out whether there is a relationship between mother's knowledge about food presentation and children's appetite Method: This research is quantitative research with a cross sectional method Results: the results of the Kolmogorof alternative chi squere test obtained a value of p= 0.023 (p<= 0.05) so it was concluded that there was a relationship between mother's knowledge about food presentation and changes in children's appetite. Conclusions and suggestions: there is a relationship between maternal knowledge and appetite in stunted children. The results of this research theoretically can be expected to provide additional knowledge and theory towards the development of nursing science to conduct further research related to the relationship between maternal knowledge about food presentation and appetite in children. stunted children